Equivalent Selection in Specialized e-Lexicography: A Case Study with Spanish Accounting Terms - Fuertes-Olivera, Pedro A. (Lexikos, 2011)
Interest in specialized lexicography has been propelled both by the development of LSP communication in academic circles and by the consolidation of function-based approaches to lexicography that have identified the existence of several user types, e.g., experts, semi-experts and interested laypersons, and use situations, typically cognitive-oriented and communicative-oriented (Bergenholtz and Tarp, 2003, 2004). This paper follows suit and elaborates on the selection of Spanish equivalents in a particular dictionary project: the Diccionario Inglés–Español de Contabilidad, one of the Accounting dictionaries. This dictionary aims to satisfy the needs of translators (primary user group), accountants and financial experts (secondary user group), as well as students of accountancy and translation, journalists, and interested laypersons (tertiary user group). It addresses the issue as a lexicographical problem and makes comments on the decisions taken by elaborating on three lexicographical principles that take into consideration the nature of lexicography, the technical options the Internet offers, and the defining characteristics of specialized discourse: relevance, proscription and recreation.